La jurisprudencia internacional como instrumento de política exterior ecuatoriana: la reparación integral en las sentencias de la corte interamericana de derechos humanos - Freire Terán, Lenin Andrés (2018)
The judgments issued by the international courts are binding on the States that have recognized their competences over them, thus constituting guidelines for the formulation of an international policy in compliance with what was ordered by said courts. The present research work seeks, through a qualitative and quantitative study, to determine what is the foreign conduct of Ecuador against the integral reparation ordered in judgment by the Inter-American Court of Human Rights from 2008 to 2017. The text develops an analysis of compliance with integral reparation establishing the theoretical requirements so that said reparation can be considered integral in the Inter-American Human Rights System. Finally, comprehensive Ecuadorian reparation measured by measure will be analyzed, contrasting what was ordered in sentences with compliance supervisions of the Inter-American Court of Human Rights.